Assessing the impact of sharing economy through adoption of ICT based crowdshipping platform for last-mile delivery in urban and semi-urban India. Issue 4 (2nd October 2021) - Upadhyay, Chandra Kant; Tewari, Vijayshri; Tiwari, Vineet
ABSTRACT: Crowdshipping and Item sharing are the concepts of sharing economy being increasingly adopted by various retailers to address the problem of last-mile delivery. Moreover crowdshipping platform has not yet been introduced commercially in developing countries successfully. Thus the purpose of this study is to investigate the Indian urban and semi-urban participant's intention toward crowdshipping platform for last-mile delivery through the use of sharing economy. A sociotechnical framework is adopted to analyse and assess the impact of sharing platform intension by considering the mediating roles of 'trust' and 'attitude'. The theoretical model has been validated empirically using a survey of 310 participants and subsequent analysis have been carried out using structured equation modelling. The result indicate increasing participation of the next generation. The research also highlights impacts of potential for collaboration with various stakeholders. As a result, it can lead to generate employment opportunities and revenue generation.